THE EFFECT OF HOME CIGARETTE SMOKE EXPOSURE TO THE RESPIRATORY DISEASES AMONG UNDERFIVES IN DENPASAR - I Made Kerta Duana (MTCC, John Hopkins n The Union, 2015)
Background: Basic Health Survey in Denpasar in 2010 found smoking behavior at home was high (68 %). The prevalence of respiratory disease always listed on the top at Primary Health Care (Puskesmas) report in Denpasar. Hence, we aimed to determine the effect of cigarette smoke exposure to the prevalence of respiratory diseases among children under age fives in Denpasar. Methods:The study is a case control study; cases awere mothers who have under-fives suffering from respiratory disease and who received treatment at Puskesmas or community health clinics in Denpasar. While controls awere mothers who have under-fives not suffering from respiratory disease and also treated during the same period as the cases at the clinics. Sample size was 140 and selected using cluster sampling. Data was collected using structured questionnaire and analyzed using statistical test Chi Square and logistic regression. Results: For the case group, it was 60% male; 14.3% had uncompleted immunization history, and 60% suffered from respiratory disease 60% which is higher than in the control group. Exposure from secondhand smoke from the father or other family members were the independent factor of respiratory diseases among under-fives. The odds ratio (OR) of 1-hour exposure a day is 2.6 (95%CI: 1.1-6.4; p value = 0,033). The OR increaseds to 5.7 (95%CI: 1.2-25.3; p value 0,021) if the duration of exposure was 2 hours or more. Moreover, based on urine cotinine examination it was found that 4 of 140 of the participants tested positive. All the positive tests were found in case group and all of them were exposed to second hand smoke for a duration of â‰¥ 2 hours by either their father or another family member. Conclusions: It is recommended relevant health care authorities undertake effort to increase health promotion activities on the harms of smoking including exposure to second hand smoke; integration of mother and child health components in smoking cessation resources. In addition, smoke free home initiative may be considered to prevent exposure to second hand smoke particularly among children. Keywords: Cigarette Smoke, Under-fives, Respiratory Diseases